Critical notes on the law regulating commercial advertising in the Kurdistan Region - Iraq No. (4) of 2019 - Latif, Adnan Baqy; Rahim, Bakhtiar Sdiq; Mahmoud, Awesta Burhan (Journal of Legal and Political Studies, 2021)
The legislator in the Kurdistan Region of Iraq worked on the legal framing of advertising content to end the era of modest regulation of this subject, whether under the Iraqi Consumer Protection Law No. (1) of 2010 or the Iraqi Advertising, Publicity and Advertising offices Law No. 45 of 1971, as amended, so he issued the “Law Regulating Commercial Advertising In the Kurdistan Region - Iraq No. (4) of 2019 “with the aim of serving the consumer, economic development, providing better services to citizens, creating healthy competition for marketing, as well as reducing the negative and harmful aspects of advertising, according to the reasons for its issuance. Although the issuance of this law is a step in the right direction, we found by looking at its contents that it includes clear legislative shortcomings in form and content that undermine many of the goals that the law was issued to achieve. Therefore, we chose to conduct this study by analyzing the articles of the law and making observations on it with a critical reading that focuses on the aspects that we believe need to be modified, added or deleted, all in order to come up with results and recommendations for the Kurdistan Region to have a modern commercial advertising law capable of keeping pace with developments.
Keywords: legislator; Law No 45 of 1971; Commercial Advertising; legislative shortcomings; Kurdistan Regio